The Role of Manufacturing Exports in the Economic Development in Malaysia - Martin, Tulasi; Muhammad Ashraf, Fauzi; Nallaluthan, Kesavan; Balasundran, Komathy (HRMARS, 2021)
The purpose of this paper is to assess the role of manufacturing exports in the growth of the Malaysian economy. The greater the growth rate of manufacturing production, the greater the overall growth rate of economic products. Regression and correlation methods were used to achieve the study objectives. Secondary data used to estimate empirical models in this study were obtained from the statistical publications of the World Bank and Asian Development Bank (ADB). The data covered the period of 1981-2015. The study findings used regression analysis indicated that there were positive and significant influences of industrial output and exports on economic growth in Malaysia. The findings used correlation analysis indicated that there was a positive and significant relationship between the level of the manufacturing sector and exports that contributes to economic growth in Malaysia. The impact of this study will be discussed in its managerial perspectives. Implications are the need of taking restructuring measures in the manufacturing sector to enhance productivity growth and exports. These factors were expected to give an important contribution to the growth of Gross Domestic Product (GDP) in Malaysia. The government has to identify the weaknesses that exist in the manufacturing sector and exports.